USE OF HYPERTONIC GLUCOSE AS A SCLEROSANT IN THE TREATMENT OF MICROVASES - Carvalho Nogarolli , Fernanda; Giacomini , Alex; Mithie Ogo , Fernanda (Health and Society, 2021)
Telangiectasias and microvessels are the most common types of varicose veins, usually their appearance is related to genetic susceptibility, normally affecting the lower limbs of the body. The PEIM (Aesthetic Injectable Procedure in Microvessels) has been widely used to eliminate telangiectasias and microvessels. Therefore, the objective was to describe the effectiveness of liquid sclerosing agents in the treatment of telangiectasias and microvessels. This work is part of a literary review covering the period between 1986 and 2020 using Scielo, Google Scholar and Pubmed platforms. Telangiectasias and microvessels generally do not present health problems, most of the time the problem is esthetic without pathological character. Currently, there are several sclerosing substances used in the treatment, in this case, hypertonic glucose is identified as one of the most used sclerosing agents, because, even though a treatment takes a little longer to obtain results, it is a little painful, the risk of complications is lower and procedure value is affordable. Although the sclerotherapy technique has been used for a long time, so far no sclerosant with absence and complications and totally effective has been discovered, even though there are case studies that report to the contrary, thus, this literature review shows that more studies are needed. to prove the efficacy and safety of hypertonic glucose.